Carbon containing material in non-woven fabrics for thermoinsulation of winter apparel - Lipik, Vitali T. (2020)
Nowadays different types of carbon containing fibers become more and more popular in textile. Pure carbon fibers, fibers with carbon particles, graphene and even carbon containing dyes began to apply in textile for different purposes. Fibers may contain from about 1% of black carbon for antistatic property up to 40% of graphene for special mechanical and moisture management properties. Carbon has pro and contra as thermoinsulating material. It possesses great ability to absorb heat but, at the same time, carbon is good thermoconductive material, and heat escapes quickly due to high thermal conductivity. Heat loss from human body is realized through several channels. For example, thermoconductive heat loss is only 10-15%, whereas irradiative heat loss can reach up to 80% from total heat loss value. Based on this information, we developed non-woven carbon containing compositions which is targeted for maximizing capture of outgoing irradiation heat and minimizing heat loss in thermoconductive channel. In this work, we presented result of development of different carbon containing non-woven compositions for insulation. As a result, some of our non-woven paddings with density 100 g/m 2 have clothing insulation value (CLO) equal 4, which makes them close to natural down insulation. We also provided wide characterizations of non-woven samples such as stiffness, IR absorption and reflection, washing stability, analysis of economic feasibility of industrial production.